A superior method for cell block preparation for fine‐needle aspiration biopsies. Issue 7 (22nd April 2016) - Balassanian, Ronald; Wool, Geoffrey D.; Ono, Jill C.; Olejnik‐Nave, Jolanta; Mah, Molinda M.; Sweeney, Brenda J.; Liberman, Hava; Ljung, Britt‐Marie; Pitman, Martha B.
Abstract : BACKGROUND: Cell block (CB) techniques for fine‐needle aspiration biopsies (FNABs) vary. A direct comparison of CB techniques with statistical validation was performed to identify the best method. METHODS: Three CB techniques were compared: 1) FNAB rinsed in saline and clotted with plasma and thrombin (SPT); 2) FNAB rinsed in formalin and clotted with HistoGel (HG); and 3) FNAB rinsed in formalin, centrifuged, and the pellet captured in a collodion bag (ColB). FNAB was performed on 35 random surgical specimens for smears and each CB technique. A randomized blinded review of hematoxylin and eosin‐stained CB slides was performed and each case was scored on a scale of 1 to 3 for cellularity, preservation, and architecture and the overall best CB was identified. Significance was determined by the Mann‐Whitney U test for nonparametric ordinal data. RESULTS: The mean cellularity score was 1.71 for SPT (standard deviation [SD], 0.89), 1.68 for HG (SD, 0.67), and 3.0 for ColB (SD, 0). The mean preservation score was 1.31 for SPT (SD, 0.58), 1.54 for HG (SD, 0.70), and 2.91 for ColB (SD, 0.37). The mean architecture score was 1.45 for SPT (SD, 0.70), 1.43 for HG (SD, 0.60), and 2.71 for ColB (SD, 0.57). There was no statistical significance noted between SPT or HG when compared for each category. ColB was found to be superior to both SPT and HG when compared for each category ( P <.05). The overall best CB was obtained with ColB in 33 of 35 cases (94%), with SPT proving superior in 1 of 35 cases (3%) and HG superior in 1 of 35 cases (3%). CONCLUSIONS: ColB appears to be a superior technique for CB, yielding greater cellularity, preservation, and architecture in the majority of cases. Cancer Cytopathol 2016;124:508–18 . © 2016 American Cancer Society . Abstract : In the current study, a statistically validated comparison of 3 different fine‐needle aspiration biopsy cell block methods (saline plasma thrombin, HistoGel, and collodion bag) is performed. The results indicate that the collodion bag is a superior technique for cell block preparations.